The design of a wireless scoring system for Epee fencing - Laurenson, C.; Redouté, J.-M. (International Journal of Sports Science and Engineering, 2012)
This paper presents a method of registering hits in the sport of fencing, specifically for Epee, without the need for wires connecting the fencer to a central scoreboard. It outlines the problems associated with the development of such a system, including the lack of a common ground between devices. The paper focuses specifically be on the development of a prototype wireless scoring system for Epee fencing, compatible with existing equipment, which can be later adapted to operate with other weapons. The design and construction approaches taken to create a prototype solution are discussed. The use of high frequency signals, and exploitation of human body capacitive effects, and their usefulness in this context are explored. The success of the design in the trials is discussed, along with the limitations, which include latency and interface complexity. Finally, the paper analyses the strengths and weaknesses of the developed system, and recommends system improvements.